Some Aspects of Retrospective Studies - Haenszel, William (Revista Brasileira de Cancerologia, 1976)
The statement that a disease and a characteristic are associated can be Tinterpreted in a number of different ways. (1) The deliberate introduction of the characteristic into a subgroup of a population will be followed by an altered incidence of the disease in that subgroup. (2) Those members of a population possessing the characteristic will experience a different incidence of the disease than will those lacking it, the route by which the characteristic was acquired being unspecified. (3) The prevalence of the characteristic among newly developed cases of the disease differs from its prevalence among those in whom the disease did not develop.